KEEPING THE FIRE BURNING: A QUALITATIVE STUDY OF INTERGENERATIONAL STRATEGIES FOR FAMILY BUSINESS SUSTAINABILITY IN AN ERA OF DISRUPTION: Menjaga Api di Perapian: Studi Kualitatif tentang Strategi Intergenerasional dalam Keberlanjutan Bisnis Keluarga di Era Disrupsi - Mohammad Syarifuddin Fatahillah; Iing Sri Hardiningrum (SOSIOEDUKASI, 2025)
This study aims to explore intergenerational strategies implemented to maintain the sustainability of family businesses amidst the era of disruption. Using a qualitative case study approach at UD. Sami Asri Tulungagung, this study reveals how the process of value inheritance, technological adaptation, and intergenerational role division are key factors in facing the changing times. Data collection techniques were conducted through in-depth interviews, participant observation, and documentation, allowing researchers to gain a comprehensive understanding of the social and cultural dynamics of family businesses. The results indicate that intergenerational dialogue, shared learning, and structural flexibility are important elements in sustainability strategies. These findings provide theoretical contributions to the study of family businesses and offer practical guidance for family business owners in facing the challenges of the era of disruption.